Transformasi Digital Dan hak Cipta: Analisis Peredaran Sinematografi Di Telegram - Kusumaningsih, Rila (Primagraha Law Review, 2025)
Digital transformation has brought significant changes in the way people access, distribute and consume cinematographic works. Telegram, as one of the digital-based communication platforms, is often used as a means of circulating cinematographic works, both legally and illegally. This article aims to analyze the dynamics of the circulation of cinematographic works in Telegram, focusing on the legal implications related to copyright infringement as well as the challenges of monitoring and law enforcement in the digital ecosystem. This study uses normative and empirical juridical approaches to identify regulatory gaps and evaluate the mitigation measures that have been implemented. The results show that Telegram is a difficult platform to monitor due to its characteristics that support user privacy and anonymity. On the other hand, users' lack of awareness of the legal implications of illegal circulation of cinematographic works exacerbates the situation. This study recommends strengthening regulations, collaboration between stakeholders, and public education as strategic steps to protect copyright in the era of digital transformation